Historiografi Pesantren di Indonesia - Fatiyah Sudarmo (UIN Sunan Gunung Djati Bandung, 2021)
The aim of this research is to describe and analyze the historiography writing style of pesantren in Indonesia. The pesantren has historically been a “genuine” model of the Islamic education system in the archipelago. At the beginning of its establishment and development, pesantren is a form of education and learning of Islamic religion (recitation assemblies) which is managed by a kiai. At this stage, the pesantren has the main elements, namely: kiai, mosques, and santri. We know this type from the name of pesantren salafiyah. Then it develops according to the times and knowledge in terms of management and learning systems as well as the knowledge being taught to develop by incorporating general knowledge, which became known as